2013
DOI: 10.1186/1471-2458-13-278
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and beverage consumption in preschoolers: focus groups with parents and teachers

Abstract: BackgroundQualitative research is a method in which new ideas and strategies can be discovered. This qualitative study aimed to investigate parents’ and teachers’ opinions on physical activity and beverage consumption of preschool children. Through separate, independent focus groups, they expressed their perceptions on children’s current physical activity and beverage consumption levels, factors that influence and enhance these behaviours, and anticipated barriers to making changes.MethodsMulti-cultural and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
135
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(147 citation statements)
references
References 52 publications
10
135
0
2
Order By: Relevance
“…However, this strategy is in contrast to parents' perceptions, because parents believe that the most effective strategy to reduce SSB consumption in younger children (preschoolers) is to model good behavior. 15 Regardless, parental involvement in education is vital because parents are naturally the most influential and trusted source of information for children about food. 38 Furthermore, because the home food environment is mainly associated with children's overall SSB consumption, 39 parental involvement and education are essential to reduce SSB consumption effectively in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this strategy is in contrast to parents' perceptions, because parents believe that the most effective strategy to reduce SSB consumption in younger children (preschoolers) is to model good behavior. 15 Regardless, parental involvement in education is vital because parents are naturally the most influential and trusted source of information for children about food. 38 Furthermore, because the home food environment is mainly associated with children's overall SSB consumption, 39 parental involvement and education are essential to reduce SSB consumption effectively in children.…”
Section: Discussionmentioning
confidence: 99%
“…11 To provide effective educational strategies to reduce SSB consumption in children, an in-depth understanding of their opinions and attitudes toward these beverages is needed. Whereas qualitative studies have been conducted with parents and teachers of preschoolers, adolescents, and young adults to elucidate attitudes toward and factors influencing SSB consumption, [12][13][14][15] to the authors' knowledge, to date, no study has assessed this qualitatively in children. Therefore, the aims of this study were to investigate (1) children's perceptions of SSBs, (2) factors influencing their SSB choice and consumption patterns, and (3) children's suggestions for reducing SSB consumption within their peer group.…”
Section: Introductionmentioning
confidence: 99%
“…Nedfaeldede politikker om bevaegelse og fysisk aktivitet øger børns daglige fysiske aktivitetsniveau og opnåelse af anbefalinger på området (Tonge et al, 2016). Paedagoger og foraeldre vurderer typisk maengden af børns fysiske aktivitet højere, end den i virkeligheden er De Craemer et al, 2013;Little & Sweller, 2015), og paedagogers vurdering af maengden af børns fysiske aktivitet kan indirekte have betydning for, hvor meget børn rent faktisk bevaeger sig. Paedagoger, der vurderer, at børn bevaeger sig tilstraekkeligt, har mindre fokus på, at børn skal bevaege sig yderligere (Coleman & Dyment, 2013).…”
Section: Paedagogen Som Rollemodelunclassified
“…1719 However, a recent qualitative study of child care providers from 6 European countries found that providers perceived children to be sufficiently active, and thought that increasing PA would hinder preparation for primary school, where children need to learn to sit still. 20 Modifiable playground characteristics, equipment use, and equipment availability were also related to the PA levels of young children. 17,2125 …”
mentioning
confidence: 99%